Is Research Experience Detrimental to a Clinical Pharmacist's Career? - Roxanna S. D. Mohammed; Eugene Y. H. Yeung (MDPI AG, 2018)
A recent article in the Canadian Journal of Hospital Pharmacy discussed pharmacists’ perception of clinical research. The article illustrated that pharmacists lack the time, resources, and skills to conduct research. In the current paper, two ex-pharmacists, who now work as physicians, commented on the prejudice towards pharmacy researchers. Pharmacy researchers face obstacles such as being mislabeled as “non-clinical” and lacking opportunities to be involved in high-impact publications. The current paper discussed ways to improve pharmacy research, including collaboration with well-established researchers, putting less emphasis on the “clinical” pharmacist title, and changing the pharmacy culture.